2017
DOI: 10.1371/journal.pmed.1002212
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Properties of Piperaquine in Falciparum Malaria: An Individual Participant Data Meta-Analysis

Abstract: BackgroundArtemisinin-based combination therapies (ACTs) are the mainstay of the current treatment of uncomplicated Plasmodium falciparum malaria, but ACT resistance is spreading across Southeast Asia. Dihydroartemisinin-piperaquine is one of the five ACTs currently recommended by the World Health Organization. Previous studies suggest that young children (<5 y) with malaria are under-dosed. This study utilised a population-based pharmacokinetic approach to optimise the antimalarial treatment regimen for piper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 54 publications
7
64
0
Order By: Relevance
“…The 95% CI is calculated as the 2.5th to 97.5th percentile of bootstrap estimates piperaquine (below 35%). The overall pharmacokinetic parameter estimates were in agreement with previous studies in healthy volunteers and patients with P. falciparum malaria [8,23,48,50,51].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The 95% CI is calculated as the 2.5th to 97.5th percentile of bootstrap estimates piperaquine (below 35%). The overall pharmacokinetic parameter estimates were in agreement with previous studies in healthy volunteers and patients with P. falciparum malaria [8,23,48,50,51].…”
Section: Discussionsupporting
confidence: 89%
“…Piperaquine was described by a three-compartment disposition model, which is in agreement with recently published studies [8,[47][48][49][50]. The variable absorption characteristics of piperaquine were best described with two transit absorption compartments, compared with three or five in previous studies [8,48].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The most likely explanation is the absence of fat-containing foods with the drug administration. 21 In the reference study on which the model was built a light meal was administered at the time of antimalarial dosing, while food intake was not monitored in the present study. 20 Intake of a high-fat meal has been seen to enhance the absorption of piperaquine while smaller amounts of fat have been shown not to have an effect.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The observed piperaquine levels were well above the threshold required to kill Plasmodium species in earlier studies, and the observed piperaquine concentrations are similar to what is seen in patients during acute treatment of uncomplicated malaria. 21 Nearly all participants reported one or more adverse events. Some participants reported 14 and more AEs suggesting a highly variable threshold for reporting AEs is in this population.…”
Section: Discussionmentioning
confidence: 99%